2017
DOI: 10.1016/j.transproceed.2017.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Later Evaluation of Ischemia and Reperfusion by the Pringle Maneuver in Wistar Rats, Demonstrating That Hepatic Lesions Can Be Reversible

Abstract: The oxidative phosphorylation system recovered with improvement in mitochondrial respiration; however, morphologic recovery was associated with the type and intensity of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Delourdes and colleagues [53] have reported that histopathological changes associated with 20 min of hepatic IRI animal models were completely reversed in the postoperative 28th day. The current research on hepatic IRI is performed on experimental models that performed ischemia between 15 to 60 min [52][53][54][55][56]. In our study, we have performed histopathologic analyses on the liver grafts harvested with and without the Pringle maneuver and liver specimens were obtained during the "Back-Table " procedures.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Delourdes and colleagues [53] have reported that histopathological changes associated with 20 min of hepatic IRI animal models were completely reversed in the postoperative 28th day. The current research on hepatic IRI is performed on experimental models that performed ischemia between 15 to 60 min [52][53][54][55][56]. In our study, we have performed histopathologic analyses on the liver grafts harvested with and without the Pringle maneuver and liver specimens were obtained during the "Back-Table " procedures.…”
Section: Discussionmentioning
confidence: 98%
“…Determination of hepatic IRI is difficult. The morphologic findings of hepatic IRI have been reported as eosinophilia, pyknosis, chromatin fragmentation, steatosis, and vacuolization [52,53]. Delourdes and colleagues [53] have reported that histopathological changes associated with 20 min of hepatic IRI animal models were completely reversed in the postoperative 28th day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the reversal of the mitochondrial lesion in the 20-minute ischemia has been described; the groups were evaluated immediately and 20 minutes after reperfusion. Improvement in mitochondrial respiration and morphological recovery directly related to the type and intensity of the lesion 24 , were observed. The surgical technique also includes hypothermic perfusion and parenchymal hypothermia, capable of reducing the inflammatory response and increasing ischemic tolerance 25 .…”
Section: Cheating the Ir Injurymentioning
confidence: 89%
“…Durante isquemia normotérmica pode ocorrer vacuolização citoplasmática, congestão sinusoidal e/ou venosa, balonização e dependendo do tempo de isquemia, focos de necrose e infiltração gordurosa 1,11,12,27,32,112 .…”
Section: Introductionunclassified